Sumbangan Pendidikan Islam Persatuan Islam (PERSIS) Dalam Implementasi Pendidikan Nasional di Jawa Barat, Indonesia: Contribution of PERSIS on Islamic education in Implementation of National Education in West Java, Indonesia - Achjadilaga, Undang; Yusoff, Abdullah (Journal Al-Muqaddimah, 2020)
Islamic Association (PERSIS) Bandung is playing some roles in Islamic education. Although many studies in term of history of PERSIS or revitalization of Pesantren PERSIS have been done by previous scholars, but studies on the contribution PERSIS in implementation of Islamic Education in line with System of National Education are not significantly contribute yet. Therefore, the objective of this paper is to study the contribution PERSIS in implementation of Islamic education in Jawa Barat (West Java) Indonesia also to discuss any levels of Islamic Education. The case study selected for this paper is PERSIS Bandung, Jawa Barat (West Java). This study is using a qualitative data from many documents as a secondary data and an interview of main sources as a primary data. The method of thematic analysis was used to analyzed the data collected. Through this method, the themes of the contribution of PERSIS in implementation of Islamic education in West Java was discussed objectively. The conclusion from this current study found that Islamic education in PERSIS has contributed significantly and has some efforts, mainly in developing institution Pesantren PERSIS from time to time.